2009
DOI: 10.1149/1.2999335
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Dopant Cations on Microstructure and Proton Conductivity of Barium Zirconate

Abstract: The effects of various cations ( Mg2+ , In3+ , Yb3+ , Tm3+ , Er3+ , Ho3+ , Gd3+ , Nd3+ , La3+ , Bi3+ , and Ga3+ ) were examined as dopants into the B site of perovskite barium zirconate. The solubility of In, Yb, Tm, Er, and Ho, whose ionic radii are close to that of zirconium ion, into the B site is more than 0.075 (normalXMO1.5=0.075) at 1600°C . In contrast, when there is a large difference of ionic radii between trivalent cations ( Nd3+ , La3+ , Bi3+ , and Ga3+ ) and zirconium ion, the solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 30 publications
(47 reference statements)
6
66
1
Order By: Relevance
“…We investigated the dopant dependency of proton conductivity of barium zirconate where Sc, In, Yb, Tm, Er, Y, Ho and Gd were examined [21]. In the investigation, we found that the minimum points of activation energy and pre-exponential terms for bulk conductivity as a function of ionic radius of dopant cation exist at around 0.087 nm as seen in Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We investigated the dopant dependency of proton conductivity of barium zirconate where Sc, In, Yb, Tm, Er, Y, Ho and Gd were examined [21]. In the investigation, we found that the minimum points of activation energy and pre-exponential terms for bulk conductivity as a function of ionic radius of dopant cation exist at around 0.087 nm as seen in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…steam electrolyzers, and many researchers are working on doped barium zirconate [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sacrifice powders were synthesized by a conventional solid state reaction. [10,[18][19][20] The heat-treatment sample temperatures were checked using a thermal history sensor (Referthomo type H, AS ONE). The temperature deviation in the experiments was within 1600 ± 10 and 1500 ± 5°C.…”
Section: Materials Preparationmentioning
confidence: 99%
“…Yttrium-doped barium zirconate is known to have the lowest protonic resistance of grain interior among trivalent cation-doped barium zirconate and this property attracts many researchers. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In the previous works, we investigated a sintering mechanism of 15% yttrium-doped barium zirconate (BaZr 0.85 Y 0.15 O 3-d ) at 1600°C based on the idea of twophase separation of yttrium poor barium zirconate and yttrium rich barium zirconate phase in the sample by conventional solid state reaction. [19,20] A phase separation at 1600°C was reported by Kojima et al [23] However, the points we discussed are that there is no phase separation in equilibrium at 1600°C, but traces of the phase separation at synthesizing temperature, 1300°C, might remain even at 1600°C.…”
Section: Introductionmentioning
confidence: 99%